The Pengaruh Inovasi Produk Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Timtam (Studi Kasus Pada Konsumen Toserba Yogya Pamanukan Kabupaten Subang) - Tedy Purwanto; Hartelina Hartelina; Hawignyo Hawignyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
A product that has innovation and quality will be able to attract consumers to make a purchase. However, this is different from the TimTam products at the Yogya Pamanukan Toserba where there is a decrease in purchasing decisions for these products. This study aims to explain the influence of the variables of innovation and product quality on the purchasing decisions of TimTam products on consumers of the Yogya Pamanukan Toserba. The variables used in this study are two independent variables (product innovation (X1) and product quality (X2)) and one dependent variable, namely purchasing decisions (Y). The types of data used in this study are primary and secondary data. This research method uses quantitative methods with data collection techniques through distributing questionnaires to Yogya Pamanukan Toserba consumers who buy TimTam products. The sampling technique of this study was proportionate stratified random sampling using the 5% slovin formula. The sample used in this study amounted to 255 respondents. The instrument test was carried out using a validity test and a reliability test. The data analysis method was carried out using descriptive statistical tests and hypothesis testing with analysis tools, namely multiple linear regression. The results showed that product innovation and product quality were perceived as good and purchasing decisions were perceived as agreeable. The results of data analysis show that product innovation and product quality partially have a significant positive effect on purchasing decisions for TimTam products and the conclusion of this study is that product innovation and product quality both have a significant influence on purchasing decisions with a very strong relationship level. Keywords: product innovation, product quality, purchasing decisions